2020
DOI: 10.1186/s12882-020-01721-z
|View full text |Cite
|
Sign up to set email alerts
|

Furosemide stress test and interstitial fibrosis in kidney biopsies in chronic kidney disease

Abstract: Background: Interstitial fibrosis (IF) on kidney biopsy is one of the most potent risk factors for kidney disease progression. The furosemide stress test (FST) is a validated tool that predicts the severity of acute kidney injury (especially at 2 h) in critically ill patients. Since furosemide is secreted through the kidney tubules, the response to FST represents the tubular secretory capacity. To our knowledge there is no data on the correlation between functional tubular capacity assessed by the FST with IF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…29 Additionally, among patients undergoing kidney biopsy for clinical indiciations, the excretion of furosemide was found to be inversely correlated with severity of interstitial fibrosis. 30 Taken together, these findings suggest that the non-invasive assessment of secretory makers may be important in bridging the gap between functional and J o u r n a l P r e -p r o o f anatomical changes in the setting of kidney injury. Our findings add to this knowledge by demonstrating that secretory solutes, reflecting proximal tubule function, are lower in the urine relative to plasma in the setting of greater histologic tubule damage, independent of GFR.…”
Section: Discussionmentioning
confidence: 83%
“…29 Additionally, among patients undergoing kidney biopsy for clinical indiciations, the excretion of furosemide was found to be inversely correlated with severity of interstitial fibrosis. 30 Taken together, these findings suggest that the non-invasive assessment of secretory makers may be important in bridging the gap between functional and J o u r n a l P r e -p r o o f anatomical changes in the setting of kidney injury. Our findings add to this knowledge by demonstrating that secretory solutes, reflecting proximal tubule function, are lower in the urine relative to plasma in the setting of greater histologic tubule damage, independent of GFR.…”
Section: Discussionmentioning
confidence: 83%
“…Additional functions of the kidney tubules are not routinely measured clinically but are measurable by research assays. These include assessment of the proximal tubules' capacity to reabsorb filtered smallmolecular-weight proteins (eg, α 1 -microglobulin [A1M]), 8 the capacity of the proximal tubule to secrete endogenous metabolites (eg, hippurate) 9 or exogenous compounds (eg, furosemide), 10 the production of proteins required to maintain impermeability of water to distal tubule segments and to protect against infection (eg, uromodulin), 11 and ammonium production as a marker of the kidney tubules' ability to excrete acid. 12 These tubule biomarkers should have direct relevance to the prognosis for kidney-specific end points and also for CKD complications such as CVD, heart failure, and mortality.…”
Section: Measures Of Tubule Injury and Dysfunctionmentioning
confidence: 99%
“…Of the 29 articles, two [32,33] were suspected of using a duplicate cohort from another study [8], five were focused on child populations [11,12,[34][35][36], and three were based on kidney transplant outcomes [9,10,37]. Meanwhile, five studies reported different outcomes of interest and the remaining three did not report sufficient information for analysis [38][39][40][41][42][43][44][45] (Additional profile 1: Supplementary Table 2). As such, eleven studies were ultimately included in this meta-analytic study (Fig.…”
Section: Literature Searchmentioning
confidence: 99%